[End of election campaign, Bob Hawke, Paul Keating, Gareth Evans, John Button] - Pryor, Geoff, 1944- (1984)
For a while, the 1984 election looks like a cliffhanger, but the Hawke Government just hangs on to power after an interminably long campaign. The image of a staggering Bob Hawke being urged on by his colleagues at the finish line is a reminder of a staggering, near-to-collapse runner in the marathon at the 1984 Los Angeles Olympic Games marathon. --Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times 29 November 1984.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Hawke, Bob, -- 1929-2019 -- Caricatures and cartoons; Evans, Gareth, -- 1944- -- Caricatures and cartoons; Button, John, -- 1933-2008 -- Caricatures and cartoons; Keating, Paul, -- 1944- -- Caricatures and cartoons; Elections -- Australia -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Federal politicians